Occurence and genotype distribution of Cryptosporidium spp., and Giardia duodenalis in sheep in Siirt, Turkey - AKYILDIZ, GÜRKAN (My University, 2023)
Cryptosporidium spp., and Giardia duodenalis are intestinal protozoan parasites known to infect humans and various animals and cause diarrhea. This study aimed at determining the prevalence and genotype of Cryptosporidium spp. and Giardia duodenalis in sheep in different locations of Siirt province. The fecal material for this study was collected from 500 sheep in different locations of Siirt province, Turkey. Fecal samples obtained from sheep were examined for Cryptosporidium spp. by Kinyoun Acid Fast staining and the Nested PCR method. Microscopic and Nested PCR methods revealed a prevalence of 2.4% (12/500) and 3.6% (18/500), respectively. Sequence analysis revealed the presence of C. ryanae, C. andersoni, and zoonotic C. parvum. In terms of Giardia duodenalis, 8.4% (42/500) and 10.2% (51/500) prevalence was determined using Nativ-Lugol and Nested PCR methods, respectively. Using sequence analysis, zoonotic assemblages A and B as well as assemblages E and D were detected. As a result of this study, both the prevalence of Cryptosporidium spp. and Giardia duodenalis and the presence of species that appear to be host-specific, as well as those known to be zoonotic, were revealed. A large-scale study is needed to understand the impact of these agents on sheep farming and their consequences on human health.
Keywords: Veteriner Bilimleri; Klinik Öncesi Bilimler; Veteriner Parazitoloji; Sağlık Bilimleri; Veterinary Sciences; Pre-Clinical Sciences; Veterinary Parasitology; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Bitki ve Hayvan Bilimleri; VETERİNERLİK BİLİMLERİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); PLANT & ANIMAL SCIENCE; VETERINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Equine; Veterinary (miscellaneous); General Veterinary; Cryptosporidium spp.; Giardia duodenalis; molecular analysis; phylogeny; sheep; Turkey